2017
DOI: 10.24193/adn.10.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitude and Competence in the Use of Assistive Technologies in Special Needs Schools

Abstract: This study examined teachers' attitude and competence in the use of assistive technologies in special needs schools. The descriptive survey method was employed for the study among 100 teachers who were drawn using purposive sampling technique from special needs schools in Osun State, Nigeria. Six research questions were generated while four hypotheses were tested at 0.05 level of significance. A researcher-constructed questionnaire tagged "Teachers' Attitude and Competence in the Use of Assistive Technology Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 8 publications
(3 reference statements)
1
15
1
3
Order By: Relevance
“…This is indeed alarming considering the significance of technology to the teaching and learning of students with disabilities. Also, this finding agreed with the finding of Onivehu, Ohawuiro, and Oyeniran (2017) which discovered that teachers of students with physical disabilities were not using assistive devices to teach because of their high-tech nature and because they were not adequately available and accessible by teachers.…”
Section: Discussion Of Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…This is indeed alarming considering the significance of technology to the teaching and learning of students with disabilities. Also, this finding agreed with the finding of Onivehu, Ohawuiro, and Oyeniran (2017) which discovered that teachers of students with physical disabilities were not using assistive devices to teach because of their high-tech nature and because they were not adequately available and accessible by teachers.…”
Section: Discussion Of Findingssupporting
confidence: 87%
“…Furthermore, the potential of high-tech assistive technologies for students with special needs is likely to be found not in the technologies themselves but in the way these technologies are used by the teachers and students as teaching and learning tools. Onivehu, Ohawuiro, and Oyeniran (2017), opined that the extent of use of assistive technologies in the classroom is determined by the attitude, experience and quality of teachers. This will require both teachers and students to get familiar with assistive devices and software available in their schools which they can use to provide needed accommodation, substitution, modifications, adjustment, and adaptations that will help special needs students to access environment, curriculum, instruction, or assessment practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that male and female teachers are equally competent in using technology, and sex is not a factor affecting technology competence. Likewise, Akturk and Ozturk (2019), Arslan (2015), Gökçek et al (2013), Kahraman and Yılmaz (2018), Onivehu, Ohawuiro andOyeniran (2017), andÖzer (2018) found that inservice teachers' sex and technology competence are not significantly related. Yielding contradicting results, Ardıç and Çiftçi (2019), Bas and Senturk (2018), Kaarakainen, Kivinen and Vainio (2018), Şimşek andYazar (2017), andTeo, Fan andDu (2015) found that male teachers outperform their female counterparts; and Anderson and Maninger (2007), Basargekar and Singhavi (2017), Buabeng-Andoh (2019) and Çakır and Oktay (2013) found vice versa.…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, workers and indeed the organization stand to gain immensely from the productive application of the internet in the workplace. In other words, the appropriate application of the internet to carry out tasks that are beneficial to the attainment of the goals of the organization could improve the level of performance, productivity and output of workers in particular and the generality of the organization (Onivehu, Ohawuiro & Oyeniran, 2017;Yıldırım & Karabey, 2017;Onivehu, Adegunju & Ohawuiro, 2018). But, on the other hand, the inappropriate use of the internet by workers in the workplace is a contemporary workplace behaviour, which is often called cyberloafing.…”
Section: Introductionmentioning
confidence: 99%